2022
DOI: 10.3390/nu14061141
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Taste and Smell Sensitivity, Preference and Quality of Life in Healthy Aging—The NutriAct Family Study Examinations (NFSE) Cohort

Abstract: Taste and smell function decline with age, with robust impairment in the very old. Much less is known about taste and smell function in young and middle aged. We investigated taste and smell sensitivity via thresholds in a sub-sample of the NutriAct Family Study (NFS), the NFS Examinations cohort (NFSE; N = 251, age M = 62.5 years). We examined different aspects relating to taste and smell function: the degree to which taste and smell sensitivity relate to another and to taste and smell preferences, the role o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
1
5
0
1
Order By: Relevance
“…The overlapping of taste and olfactory sensations during sensory tests has been frequent, but this has not always implied a simple, unchanging relationship. This was confirmed in the latest work by Lim et al [52], which demonstrated the independence of taste and smell in young and middle-aged subjects despite their overlapping during sensory experiments.…”
Section: Discussionsupporting
confidence: 66%
“…The overlapping of taste and olfactory sensations during sensory tests has been frequent, but this has not always implied a simple, unchanging relationship. This was confirmed in the latest work by Lim et al [52], which demonstrated the independence of taste and smell in young and middle-aged subjects despite their overlapping during sensory experiments.…”
Section: Discussionsupporting
confidence: 66%
“…Women tend to have higher olfactory abilities than men (Sorokowski et al., 2019 ), and this is more pronounced among young and middle‐aged adults aged 18−50 (Wang et al., 2019 ). While some studies did not report gender differences in gustatory ability (Abeywickrema & Navaratne, 2018 ; Wang et al., 2020 ), others reported that women have a superior gustatory ability to men (Huang et al., 2022 ; Landis et al., 2009 ; Lim et al., 2022 ; Michon et al., 2009 ). Based on these findings, this study only included female participants.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in stimulus sensitivity may be the greater, the longer the exposure time and the higher the stimulus concentration. A high-fat diet can lead to habituation and the need to increase stimulus levels to the desired quality in the mouth, leading to an increase in dietary fat intake and weight gain ( 29 , 43 ). In Di Patrizio studies, both slim and obese people on a 4-week low-fat diet showed a higher taste sensitivity to fatty acids compared to the state at the beginning of the experiment ( 44 ).…”
Section: Discussionmentioning
confidence: 99%